ANALISA KETEPATAN ENCODER PADA SISTEM STEERING AUTONOMOUS ELECTRIC CAR METODE PULSE COUNTER: Teknik Elektro - Romadhon, M. Rizki; Amperawan; Nawawi, Muhammad (JURNAL TELISKA, 2023)
The encoder in the steering system of an Autonomous electric car is a component used to determine the direction andposition of the racksteer displacement in the Autonomous electric car itself. The advantage of the encoder in this steeringsystem is its ability to read the number of rotations and direction of rotation of the car's steering wheel through pulsereadings from both channels of the encoder, without the need for additional specialized sensors. The data generated by theencoder is then used as a reference to ensure that the racksteer position is in the correct position during automatic controlin autonomous driving mode. Automatic control in an Autonomous electric car is achieved by reading the car's positionrelative to the road using lane detection methods through digital image processing on Raspberry Pi 4. The results of imageprocessing provide data such as direction and speed required by the car to accelerate when approaching or exiting a turn.The data from Raspberry Pi 4 is then received by the microcontroller to command the motor on the racksteer, taking intoconsideration the previous position of the racksteer obtained through the encoder.